Analysis of Role Performance and Effectiveness of Dairy Extension Service Providers in Karnataka State - Subash, Somasekaran; V, Girish; MCA, Devi; Sivaram, Muniandy (Indian Journal of Dairy Science, 2021)
Dairy extension services delivery system providing access to services and critical inputs plays a cardinal role in adoption of technologies by the farmers for improved livestock productivity. In a pluralistic environment, multiple dairy extension service providers extends various services and inputs to the dairy farmers. In this context, the present study was undertaken to assess the role performance of various dairy extension service providers and their effectiveness in Karnataka State. A total of 400 dairy farmers who were availing the services from different extension service providers were selected as respondents for the study using multi-stage random sampling method. The Department of Animal Husbandry and Veterinary Services (DAH&VS) of the State played a predominant role in providing ‘breeding services’ (87.25% A.I & 90.00 P.D), ‘preventive services’ (vaccination 86.00%, deworming 89.00%, and 76.00% disease surveillance) and ‘curative services’ (82.50%). Whereas, the Dairy Co-operative Societies (DCS) played a vital role in extending assured ‘marketing services’ (94.00%), ‘input services’ (fodder seeds 86.50%, feed supplements 89.25%), ‘implementation of dairy development schemes’ (86%) and provision of ‘extension advisory & training services' (84.50%). The effectiveness of service providers as perceived by the dairy farmers as per the weighted mean score indicates that DAH&VS was found more effective in extending ‘health care services’ (278.67) and ‘breeding & reproduction services’ (274.26), whereas, DCS were more effective in extending assured ‘marketing services’ (289.73), providing ‘input support services’ (278.33), ‘implementation dairy development schemes’ (274.53) and provision of ‘extension advisory & training services’ (264.35). The present study concludes that most of the dairy extension service providers played a significant role in extending different dairy extension services and inputs to the farmers. However, concerted efforts need to be made by all the stakeholders for possible convergence among them in reaching out to the dairy farmers and providing emphasis on ‘dairy extension education services’ in addition to ‘providing inputs & support services’ to the dairy farmers.